2013
DOI: 10.1121/1.4798648
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diffuse reflections on spatial discrimination in a simulated concert hall

Abstract: This letter presents results from a study on diffusive architectural surfaces and auditory perception. Spatial discrimination of multiple sources is investigated in a simulated performance venue with various diffusive surface treatments. Simulations were generated with closely spaced sound sources on the stage of a concert hall and a listener in the audience area. Subjects were asked to distinguish signals in which pairs of simultaneous talkers were presented at various lateral separations, in halls with flat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In other words, the experiment revealed that discriminating the lateral arrangement of two speech sources is possible at narrower separation angles when reflections come from flat or absorptive rather than diffusive surfaces. With the simulated hall all 11 early reflections were treated with measured or simulated diffusors, and again the result was the same, the separation of male and female speakers was easier when the reflections were from the flat surfaces and diffusors hinder the subjects' ability to hear which one of the speakers was on the left (Robinson et al, 2013a).…”
Section: The Quality Of Early Reflectionsmentioning
confidence: 96%
“…In other words, the experiment revealed that discriminating the lateral arrangement of two speech sources is possible at narrower separation angles when reflections come from flat or absorptive rather than diffusive surfaces. With the simulated hall all 11 early reflections were treated with measured or simulated diffusors, and again the result was the same, the separation of male and female speakers was easier when the reflections were from the flat surfaces and diffusors hinder the subjects' ability to hear which one of the speakers was on the left (Robinson et al, 2013a).…”
Section: The Quality Of Early Reflectionsmentioning
confidence: 96%